Korespondensi Fonemis Bahasa Palembang dan Bahasa Riau - Riris Tiani (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
This study aims to describe the linguistic situation and the phonemic correspondence formula from Palembang and Riau language.  The research method uses language grouping method with phonemic correspondence techniques. Palembang language and Riau language are languages derived from the same family, namely the Austronesian family. Language kinship is proven not only from the geographical location that is close together, but also evidenced in some gloss that has kinship in the field of phonemic correspondence. The phonemic correspondence formula can be seen between the Palembang language and the Riau language showing regular phonemic forms of correspondence in the form of vowels and consonants. The phonemic correspondence formulas in Palembang  and the Riau languages obtained are: / r ~ ᴓ /, / a ~ o /, / ǝ ~ a /, / j ~ t /. Phonemic vocal and consensus correspondence occurs in open and closed peultima positions.